The Effect of Ginseng on Fatigue Related to Neuromyelitis Optica Spectrum Disorder: A Double-Blinded Randomized controlled Clinical Trial - Sara Aslzadeh; Shaghayegh Shahmirzaei; Mohammad Ali Sahraian; Razieh Sadat Kazemi Mozdabadi; Hossein Rezaei Aliabadi; Mohammad Reza Gheini; Nasim Rezaeimanesh; Sharareh Eskandarieh; Fazeleh Majidi; Abdorreza Naser Moghadasi (Babol University of Medical Sciences, 2024)
Background: The effects of ginseng on fatigue have been proven in patients with multiple sclerosis (MS), which have several similar manifestations to neuromyelitis optica spectrum disorder (NMOSD) patients. This study was designed to evaluate the effects of ginseng on fatigue in NMOSD patients. Methods: In this double-blinded randomized controlled clinical trial, 64 patients were recruited and were allocated into two study groups (ginseng or placebo) via block randomization. The participants received either 250-mg ginseng or placebo twice daily for a 3-month period. Also, the measurement of outcome was performed using the valid and reliable Persian version of fatigue severity scale (FSS) questionnaire, which was filled by patients once after enrollment in the study and once at the end of the study post-intervention. Results: In total, 58 patients finished the study with no major side effects. There were no significant differences in demographic, clinical, as well as FSS between two study groups (p>0.05). Ginseng supplementation significantly reduced fatigue (40.21±13.51 vs. 28.97±14.18; p˂0.01), while patients in the placebo group showed significantly higher fatigue score after 3 months post-intervention (35.03±13.51 vs. 38.79±12.27; P: 0.02). The extent of changes in the fatigue score in the ginseng group was significantly greater than in the placebo group (p ˂0.01). Conclusion: This study revealed positive effects of ginseng on reducing fatigue in NMOSD patients with no major side effects. In this regard, further studies are warranted to evaluate and clarify the effects of ginseng on fatigue in NMOSD.